Kidney Transplantation Significantly Improves Patient and Graft Survival Irrespective of BMI: A Cohort Study. Issue 9 (3rd July 2015) - Krishnan, N.; Higgins, R.; Short, A.; Zehnder, D.; Pitcher, D.; Hudson, A.; Raymond, N. T.
<x xml:space="preserve">Abstract</x> Obesity and end‐stage renal disease (ESRD) are on the increase worldwide. Kidney transplantation is the treatment of choice for ESRD. However, obesity is considered a contraindication for transplantation. We investigated the effect of BMI on mortality in transplanted and patients remaining on the waiting list in the United Kingdom. We analyzed the UK Renal Registry (RR) and the National Health Service Blood and Transplant (NHSBT) Organ Donation and Transplantation data for patients listed from January 1, 2004 to December 31, 2010, with follow‐up until December 31, 2011. Seventeen thousand six hundred eighty‐one patients were listed during the study period, with BMI recorded for 13 526 (77%). One‐ and five‐year patient survival was significantly better in all BMI bands (<18.5, 18.5–<25, 25–<30, 30–<35, 35–<40, and 40+kg/m2) in the transplant group when compared to those who remained on the waiting list (p < 0.0001). The analyses were repeated excluding live donor transplants and the results were essentially the same. On analyses of patient survival with BMI as a continuous variable or using 5 kg weight bands, there was no cut‐off observed in the higher BMI patients where there would be no benefit to transplantation. For transplanted patients (N = 8088), there was no difference in patient or graft survival between the defined BMI bands. Thus, irrespective of BMI, patient survival is improved if transplanted.